(E)-2-Amino-4-(3,3-dimethyl-2-oxobutylidene)-1-[2-(2-hydroxyethoxy)ethyl]-6-methyl-1,4-dihydropyridine-3-carbonitrile - Hyung Jin Kim; Young Hyun Kim; Enkhzul Otgonbaatar; Chee-Hun Kwak (Acta Crystallographica Section E, 2012)
In the title compound, C17H25N3O3, there are intramolecular hydrogen bonds between an amine H atom and the epoxy O atom, and between a dihydropyridine ring H atom and the ketone O atom. In the crystal, molecules are linked into a zigzag chain running parallel to the c axis by hydrogen bonds between the hydroxy group and the ketone O atom. There are also weak C—H...O and C—H...π interactions which link the molecules into sheets lying in the bc plane.